Drug-eluting balloons in patients with non-ST elevation acute coronary syndrome. Issue 3 (March 2015) - Besic, Kristina Maric; Strozzi, Maja; Margetic, Eduard; Bulum, Josko; Kolaric, Branko
Abstract: Background: We compared efficacy of bare-metal stent (BMS) and drug-eluting balloon (DEB) combination vs BMS alone, in patients with non-ST elevation acute coronary syndrome treated with percutaneous coronary intervention (PCI). Methods: Patients with non-ST elevation myocardial infarction (NSTEMI) or unstable angina (UA) were randomized to BMS only or BMS + DEB group. Angiographic follow-up was performed after 6 months. The primary endpoints were binary in-stent restenosis (ISR) and late lumen loss (LLL) and the secondary endpoints were target lesion revascularization (TLR), stent thrombosis (ST), and new acute coronary syndrome (ACS). Results: A total of 85 patients were enrolled, 44 (BMS) and 41 (BMS + DEB). The median age was 67 (36–84) years and 68 (80%) were male. Fifty-two patients (61.2%) had NSTEMI and 33 patients (38.8%) UA. There was no difference in patient demographics, risk factors, and clinical characteristics, except for more smokers in the BMS + DEB group 18/41 (43.9%) vs 9/44 (20.5%). At follow-up, no significant difference in binary ISR was found; p = 0.593, but LLL was significantly lower in the BMS + DEB group 0.68 (0.00–2.15) mm vs 0.22 (0.00–2.35) mm; p = 0.002. The difference in major adverse cardiac events (MACE) rate combining TLR, ST, and ACS, between the groups was also non-significant, 29.5% (BMS) vs 24.4% (BMS + DEB); p = 0.835. One patient had a subacute ST (BMS + DEB) due to clopidogrel resistance. Conclusion: Patients treated with BMS + DEB combination for non-ST elevation acute coronary syndrome had significantly less LLL in comparison to patients treated with BMS alone but without an impact on patient clinical outcomes.